Dari Desa untuk Kepala Desa: Bagaimana dengan Masyarakat? - Rusnaedy, Zaldi; Dian Lestari (Ministry of Home Affairs, 2025)
The objective of this study was to examine the misuse of the village funds by village heads and to assess the benefits of the funds. Data were collected using online research methods (ORMs), including reports from supervisory agencies, news articles, and publications related to the misuse of village funds. The results showed that village funds—introduced in 2015—totaled Rp 609 trillion from 2015 to 2024, with corruption cases rising annually throughout this period. In 2023, the village sector recorded the highest number of corruption cases among all sectors. Between 2016 and 2022, a total of 682 cases were documented, resulting in state losses of Rp770.5 billion. Based on these findings, we conclude that corruption is likely to continue rising annually, particularly following the enactment of Law No. 3 of 2024, which extended the term of office for village heads from six to eight years. This prolonged tenure increases the risk of further misuse of village funds by village heads and officials. Moreover, the findings indicate that village funds have not yet been effectively used to empower communities or to significantly reduce poverty. To optimize the role of village budgets in reducing poverty and improving community welfare, the government should enhance oversight and evaluation mechanisms while implementing preventive policies to mitigate the risks associated with extending the term of office of village heads.